Implementation of an advanced algorithm for enhanced signal analysis in electrical resistance tomography using the EIDORS toolbox - Adetunji, Olubode Caleb (Centre for Bioprocess Engineering Research, 2014)
The primary objectives of this research include an implementation of a 3-D algorithm in visualising the movement of solid suspended objects through image reconstruction and assessment of the quality of these images as well as validation of the application of the 3-D algorithm in visualising the movement of conductive solution.